Dengue Fever-Associated Maculopathy and Panuveitis in Australia - K. G.-J. Ooi; H. Inglis; N. Paramanathan; J. A. Downie; M. P. Hennessy (Case Reports in Ophthalmological Medicine)
Purpose. To describe a case of dengue fever-associated maculopathy and panuveitis to raise awareness of these ophthalmic complications of dengue in Australia in the light of recent increasing numbers of outbreaks from equatorial through to tropical Australia. Case Report. A 37-year-old Caucasian Australian male returning from Cambodia presented with a bilateral dengue fever-associated maculopathy with left panuveitis diagnosed clinically and haematologically. Automated perimetry revealed bilateral paracentral scotomas while optical coherence tomography demonstrated the maculopathies to be of the diffuse retinal thickening type in the right eye and acute macular neuroretinopathy (AMN) type in the left eye. He was treated conservatively with only topical steroids and cycloplegia and made a full clinical visual recovery. Conclusion. Our case study underscores the importance of the awareness of the ophthalmic complications of dengue fever as despite their rarity they can be potentially sight threatening. The incidence of these complications is likely to rise in Australia with increased global warming and the distribution of Aedes aegypti into subtropical Australia.